2022
DOI: 10.3389/fbioe.2021.788622
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Oxidation of Ca-Lignosulfonate and Kraft Lignin in Different Lignin-Laccase-Mediator-Systems and MDF Production

Abstract: Laccase-mediator-oxidized lignin offers replacement for conventional chemical binders to produce fiberboards. Compared to the previously reported laccase–mediator system (LMS), a lignin-laccase-mediator-system (LLMS) has an advantage in that it requires much shorter fiber-enzyme incubation time due to significantly increased redox reactions. However, the cost of regularly applying laccase on an industrial scale is currently too high. We have employed CcLcc5 from cultures of the basidiomycete Coprinopsis cinere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 103 publications
(225 reference statements)
0
6
0
Order By: Relevance
“…For example, it could be applied to develop a laccase-mediator-system (LMS) to improve the low redox potential of laccase itself [28][29][30]. Euring et al evaluated the performance of different natural mediators in enzymatic oxidation of lignin by comparing oxygen consumption rates in different LMS [29]. It found that the mediator, 2,6-DMP, signi cantly enhanced the oxidation of lignosulfonate and Indulin AT with a more decrease in oxygen saturation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it could be applied to develop a laccase-mediator-system (LMS) to improve the low redox potential of laccase itself [28][29][30]. Euring et al evaluated the performance of different natural mediators in enzymatic oxidation of lignin by comparing oxygen consumption rates in different LMS [29]. It found that the mediator, 2,6-DMP, signi cantly enhanced the oxidation of lignosulfonate and Indulin AT with a more decrease in oxygen saturation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, comparing oxygen consumption might be an obvious criterion for evaluating enzyme activity. For example, it could be applied to develop a laccase-mediator-system (LMS) to improve the low redox potential of laccase itself [28][29][30]. Euring et al evaluated the performance of different natural mediators in enzymatic oxidation of lignin by comparing oxygen consumption rates in different LMS [29].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, comparing oxygen consumption might be an obvious criterion for evaluating enzyme activity. For example, the technique could be applied to develop a laccase-mediator-system (LMS) to improve the catalytic efficiency of the enzyme (Kirsch et al 2015 ; Euring et al 2022 ; Hilgers et al 2018 ). On the other hand, Euring et al ( 2022 ) evaluated the performance of different natural mediators in the enzymatic oxidation of lignin by comparing oxygen consumption rates in different LMS and found that the 2,6-DMP mediator significantly enhanced the oxidation of lignosulfonate and Indulin AT with a big decrease in oxygen saturation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the technique could be applied to develop a laccase-mediator-system (LMS) to improve the catalytic efficiency of the enzyme (Kirsch et al 2015 ; Euring et al 2022 ; Hilgers et al 2018 ). On the other hand, Euring et al ( 2022 ) evaluated the performance of different natural mediators in the enzymatic oxidation of lignin by comparing oxygen consumption rates in different LMS and found that the 2,6-DMP mediator significantly enhanced the oxidation of lignosulfonate and Indulin AT with a big decrease in oxygen saturation. On the other hand, the oxygen consumption of LMS with the help of ABTS was faster than that of 1-hydroxy-benzotriazole (HBT) supported-LMS in the oxidation of GGGE (Hilgers et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the method by which they are obtained, the residual lignin products, i.e., technical lignins, are sulfate (Kraft) lignin, sulfite lignin (lignosulfonate), organosolv lignin and hydrolysis lignin. Although Kraft lignin is the most widespread globally, much of it is burned in the factories where it is obtained, which regenerates some of the chemical reagents used and produces heat and energy [30,31]. The main drawbacks for using lignosulfonates in wood adhesive formulations are related to the higher number of impurities, e.g., high sulfur and ash content, compared to the Kraft lignin, and the deteriorated hydrophobic properties of the wood-based panels, so it is recommended to be used in combination with synthetic binders with or without additional cross-linking [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%